Saved by the VAC: Minimally Invasive Removal of a Surely Fatal Right Heart Thrombus in a Patient with Advanced Heart Failure - James Keeton; Pedro Engel Gonzalez; Julie Cox; Robert M. Morlend; Alpesh A. Amin; Pradeep P. A. Mammen; Lynn C. Huffman; Faris G. Araj (Case Reports in Cardiology)
Intracardiac thrombi are associated with an increased morbidity and mortality due to their unpredictability and embolic potential. Right heart thrombus is infrequently encountered in clinical practice outside the scenario of acute pulmonary embolism with hemodynamic compromise, and even more uncommon is the presence of a massive right heart thrombus. Embolic potential is high, and historically, management has revolved around open surgical removal or systemic thrombolysis. We hereby present a case of a massive right heart thrombus in a high surgical risk patient, which was successfully removed using a percutaneous aspiration device.